A study on the efficiency and success of HR outsourcing - Chaturvedi, Amitabh (2020)
Human resource outsourcing means that HR functions and activities are contracted to an external organization i.e., an external party bound by a contract manages and performs the human resource processes and activities. It is crucial that the right and appropriate functions are outsourced and the balance in-house HR functions left are necessary, strategic and core to the Organization. The purpose of this research is to discuss the factors which need to be considered to arrive at an effective and successfully measurable HR outsourcing decision. To explore the factors which affect the HR outsourcing decision a review of the existing literature was done to understand organizational need of focusing on core business activities, cost reduction and achieving competitive effectiveness. The two theories of HR outsourcing viz., Transactional Cost Economics and Core Competencies have been discussed in detail in the literature review. Qualitative research methodology was followed and data was collected through interviews, causal discussions, social media and desk research, etc. The data has been qualitatively explored, analyzed, interpreted, and described. The discussion summarizes the determinants and the drivers of HR outsourcing and recommends steps to achieve competitive and successful HR outsourcing. This research concludes with the note that it is the HR function’s performance and not the HR function’s responsibility that is outsourced.